Effect of Anti-Tuberculosis Multi Drug Resistance Regimen on Hematological Lung Tuberculosis Patients Profile with Multi Drug Resistance - Putra, Pradana Maulana (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: ATD administration of tuberculosis in combination and duration often causes multi drug resistance (MDR) ATD due to discontinuation of treatment. Reported hematologic abnormal changes due to ATD. This study investigated hematological changes before and during MDR therapy of MDR TB patients in Tuberculosis MDR RSUD Ulin Banjarmasin from September to December 2017. The study population was patients treated in TB MDR Poly and selected samples with a time-limiting method. Inclusion and exclusion criteria were MDR-TB patients detected by Gene Xpert® examination, treated <30 days, between 18 and 65 years of age, HIV negative, as well as identification and laboratory data recorded in the complete medical record. 17 samples collected by hematological parameters were collected. There were significant changes in hemoglobin, hematocrit, platelets, RDW-CV, MCV, eosinophils, lymphocytes, granulocytes, and monocytes after treatment. It was concluded that MDR regimen ATD did not cause anemia and thrombocytopenia. There was also no significant change in WBC even though the count of the species changed significantly Keywords: Tubeculosis, Multi Drug Resistency (MDR), Anti Tuberculosis Drugs (ATD), profil hematologis